Chemical education and research in Nepal - Dhoubhadel, Shiva P. (Himalayan Journal of Sciences, 2006)
For the successful economic growth, Nepal needs to be transformed from a commodity based economy to manufacturing based economy and a minimum of 20% of total manufacturing output should be maintained by chemical industries. Himalayan Journal of Sciences 1(1): 4-6, 2003 The full text is of this article is available at the Himalayan Journal of Sciences website